THE ROLE OF ARTIFICIAL INTELLIGENCE AND ROBOTICS IN PRIMARY EDUCATION: INNOVATIVE PEDAGOGICAL APPROACHES IN FINLAND AND UZBEKISTAN - A. T. Baltayeva (Sciental Journals Publishing, 2025)
This article analyzes the implementation of artificial intelligence (AI) and robotics technologies in primary education and the changes in pedagogical approaches. Today, the education system is not only aimed at increasing students' knowledge but also at preparing them for the competencies of the 21st century by introducing new methods and technologies. Finland is one of the leading countries in the world for effectively applying technologies and implementing innovative pedagogical methods. In this country, the integration of artificial intelligence and robotics into primary education helps to develop students' creative and analytical thinking skills. In Uzbekistan, the integration of artificial intelligence and robotics technologies into the education system is still in the early stages, but significant steps are being taken to modernize the educational process with these technologies. They offer great potential to make the learning process interactive and effective. This article examines the impact of artificial intelligence and robotics on pedagogical methodology, teachers' readiness to use technologies, students' academic achievements, and the effectiveness of using these technologies in education. In Finland, the process of integrating technologies involves regular teacher training and the adoption of new pedagogical methods. Uzbekistan is also taking steps to implement innovative methods and technologies, but this process is still under development. The article focuses on the in-depth analysis of how artificial intelligence and robotics technologies affect students' intellectual and cognitive development in primary education, as well as the renewal of pedagogical methodologies. It also examines the challenges in implementing these technologies in the educational process and ways to address them.
Keywords: Primary education, Artificial intelligence, Robotics, Finland's education system, Uzbekistan's education system, Pedagogical methodology, Innovative pedagogy, Educational technologies, Teacher qualifications, Cognitive development, Educational innovations, Students' academic achievements.